The Aspergillus fumigatus Protein GliK Protects against Oxidative Stress and Is Essential for Gliotoxin Biosynthesis - Lorna Gallagher; Rebecca A. Owens; Stephen K. Dolan; Grainne O’Keeffe; Markus Schrettl; Kevin Kavanagh; Gary W. Jones; Seán Doyle (2012)
ABSTRACT The function of a number of genes in the gliotoxin biosynthetic cluster ( gli ) in Aspergillus fumigatus remains unknown. Here, we demonstrate that gliK deletion from two strains of A. fumigatus completely abolished gliotoxin biosynthesis. Furthermore, exogenous H 2 O 2 (1 mM), but not gliotoxin, significantly induced A. fumigatus gliK expression ( P = 0.0101). While both mutants exhibited significant sensitivity to both exogenous gliotoxin ( P < 0.001) and H 2 O 2 ( P < 0.01), unexpectedly, exogenous gliotoxin relieved H 2 O 2 -induced growth inhibition in a dose-dependent manner (0 to 10 μg/ml). Gliotoxin-containing organic extracts derived from A. fumigatus ATCC 26933 significantly inhibited ( P < 0.05) the growth of the Δ gliK 26933 deletion mutant. The A. fumigatus Δ gliK 26933 mutant secreted metabolites, devoid of disulfide linkages or free thiols, that were detectable by reverse-phase high-performance liquid chromatography and liquid chromatography-mass spectrometry with m/z 394 to 396. These metabolites ( m/z 394 to 396) were present at significantly higher levels in the culture supernatants of the A. fumigatus Δ gliK 26933 mutant than in those of the wild type ( P = 0.0024 [fold difference, 24] and P = 0.0003 [fold difference, 9.6], respectively) and were absent from A. fumigatus Δ gliG . Significantly elevated levels of ergothioneine were present in aqueous mycelial extracts of the A. fumigatus Δ gliK 26933 mutant compared to the wild type ( P < 0.001). Determination of the gliotoxin uptake rate revealed a significant difference ( P = 0.0045) between that of A. fumigatus ATCC 46645 (9.3 pg/mg mycelium/min) and the Δ gliK 46645 mutant (31.4 pg/mg mycelium/min), strongly suggesting that gliK absence and the presence of elevated ergothioneine levels impede exogenously added gliotoxin efflux. Our results confirm a role for gliK in gliotoxin biosynthesis and reveal new insights into gliotoxin functionality in A. fumigatus .